Genomics in Personalized Dental Care (Update Dental College Journal, 2024)
The integration of genomics into dental care marks the advent of precision dentistry, offering transformative potential in diagnosis, prevention, and treatment of oral diseases. Dental practitioners can discover predispositions to diseases including dental caries, periodontal disease, and oral cancer and use this knowledge to tailor treatment. Customized therapies, early interventions, and preventative measures are made possible by genomic insights, which greatly enhance patient outcomes. To guarantee equal access, this encouraging change must address ethical issues, privacy concerns, and financial obstacles. With the progress of research and the growth of multidisciplinary collaborations, dentistry is set to usher in a new era of oral health management by providing more accurate, efficient, and customized patient treatment.Update Dent. Coll. j: 2024; 14(1):1-3